2021
DOI: 10.5194/acp-2021-757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameterising cloud base updraft velocity of marine stratocumuli

Abstract: Abstract. The number of cloud droplets formed at the cloud base depends both on the properties of aerosol particles and the updraft velocity of an air parcel at the cloud base. As the spatial scale of updrafts is too small to be resolved in global atmospheric models, the updraft velocity is commonly parameterised based on the available turbulent kinetic energy. Here we present alternative methods through parameterising updraft velocity based on high-resolution large eddy simulation (LES) runs in the case of ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…While the importance of sea spray emission temperature dependence has been pointed out by several sources (Grythe et al, 2014;Liu et al, 2021;Mårtensson et al, 2003), its magnitude and even direction differs between different parameterizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the importance of sea spray emission temperature dependence has been pointed out by several sources (Grythe et al, 2014;Liu et al, 2021;Mårtensson et al, 2003), its magnitude and even direction differs between different parameterizations.…”
Section: Discussionmentioning
confidence: 99%
“…Grythe et al (2014) compared a number of sea spray emission schemes and showed that the emitted mass fluxes can differ by more than an order of magnitude with strong disagreements in emitted size distributions and the wind speed and sea surface temperature (SST) dependence of the emission. Observations and model-measurement comparisons support the growth of sea salt mass flux with increasing SST (Jaeglé et al, 2011;Liu et al, 2021;Sofiev et al, 2011) and point out the importance of including it in model parameterizations. However, the case is not clear for the particle number flux that mostly consists of small particles.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation